Understanding Online Word of Mouth Phenomenon Amongst Teenagers in Thailand - Chaiwongkachon, Boontida (2008)
Word of mouth (WOM) has long been justified as a dominant force to influence consumer attitudes and purchase intention. Previous studies in WOM research area have investigated in various mainstreams such as causes and effects of WOM, factors that influence the effectiveness of WOM and characteristics of WOM participants. In the early 2000, numbers of studies have extended traditional WOM knowledge into a more contemporary area, online word of mouth (online WOM). Nevertheless, the topic of online WOM is still under scrutiny. Moreover, there are limited numbers of WOM researches outside Western context to be explored. This present study aimed to provide a more understanding of antecedents of online WOM among Thai teenagers, who are a core participant of online WOM phenomena in Thailand. Both intrinsic motivational factors and environmental factors were tested. The goal was also to find a relationship between online WOM and consumer attitudes and purchase intention. Moreover, research respondents were categorized into two groups, opinion leader and non opinion leader, in order to find their hidden rationales that initiate online WOM. The study discovered that only intrinsic motivational factors, which are altruism toward fellow consumers and seeking advice, influence on the initiation of online WOM among Thai teenagers. However, there is no relationship between online WOM and their attitudes and purchase intention. The results of this study will shed some light on online WOM process among teenagers outside the Western context. It will allow academics to better understand the complication of online WOM phenomena and further develop future research in this area. Moreover, it could help marketers working with teen segments to understand forces that encourage their targets to transmit positive and negative online WOM. Implications for marketers are also addressed.